About the Dependence of Breakthrough Curves on Flow Direction in Column Experiments of Transport across a Sharp Interface Separating Different Porous Materials. (6th May 2019) - Giacobbo, Francesca; Giudici, Mauro; Da Ros, Mirko
Abstract : Conservative transport experiments with layered porous materials (coarse-grained vs. fine-grained) were performed through experimental cylindrical columns to assess the possible occurrence of interface processes at the discontinuity between media with different hydrodynamic and hydrodispersive properties, as proposed by some authors in the past based on modelling and experimental results. The outcomes of the present work show that, under certain conditions, the breakthrough curves (BTCs) obtained for flow through the coarse-grained and then through the fine-grained media (CtF) or vice versa (FtC) can differ. More specifically, an asymmetric behaviour is observed for cases when the ratio between the column and grain diameters is small. Moreover, the discrepancies between CtF and FtC BTCs are enhanced for low flow rates and low quantity of injected solute.